2017
DOI: 10.1136/acupmed-2016-011080
|View full text |Cite
|
Sign up to set email alerts
|

Electroacupuncture Ameliorates Abnormal Defaecation and Regulates Corticotrophin-Releasing Factor in a Rat Model of Stress

Abstract: ObjectiveTo examine the effect of electroacupuncture (EA) treatment on abnormal defaecation in a rat model of chronic heterotypic stress (CHS) and investigate the underlying mechanisms.Methods20 male Sprague-Dawley rats were randomly divided into three groups: normal (n=6), CHS (n=7), and CHS+EA (n=7). Rats in the CHS group and CHS+EA groups received four different types of stressors for 7 days. For rats in the CHS+EA group, EA was applied at ST36 in the bilateral hind legs for 30 min before each stress-loadin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
9
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 27 publications
1
9
1
Order By: Relevance
“…CRHR1 and CRH elevation induced by hepatectomy was alleviated by EA. The same result was also found in cold stress (Eshkevari et al, 2013 ), chronic heterotypic stress (Zhao et al, 2017 ) and CUMS (Le et al, 2016 ), which demonstrated a role for EA in the HPA axis regulation.…”
Section: Discussionsupporting
confidence: 66%
“…CRHR1 and CRH elevation induced by hepatectomy was alleviated by EA. The same result was also found in cold stress (Eshkevari et al, 2013 ), chronic heterotypic stress (Zhao et al, 2017 ) and CUMS (Le et al, 2016 ), which demonstrated a role for EA in the HPA axis regulation.…”
Section: Discussionsupporting
confidence: 66%
“…Acupoints of ST36 (Zusanli) on bilateral hind limbs were used for EA treatment. 29 The acupoint of ST36 in rats is located 10 mm below the knee joint and 5 mm lateral to the anterior tubercle of the tibia. Acupuncture needles at each hind limb were inserted as follows: one into the ST36 acupoint and the other one 5 mm below the ST36 acupoint (5 mm in depth).…”
Section: Ea Treatmentmentioning
confidence: 99%
“…Rats in each group were consciously restrained in a wooden holder. As described in our previous study, 15 EA treatment was applied at ST36 in the bilateral hind limbs of rats, located 10 mm below the knee joint and 5 mm lateral to the anterior tubercle of the tibia. Acupuncture needles were inserted bilaterally at ST36 to a depth of 5 mm and connected to an EA apparatus (HANS-200A).…”
Section: Ea Proceduresmentioning
confidence: 99%
“…Interestingly, electroacupuncture (EA) has been reported to have a regulatory role in the modulation of CRF receptors in the amygdala and hypothalamus. 13,14 In addition, our previous study showed that EA significantly attenuated stress-induced abnormal defecation in a rat model of chronic stress; 15 Sprague-Dawley (SD) rats were exposed to chronic heterotypic stress (CHS), which involved a combination of different types of stressors and resulted in accelerated colorectal motility with excessive defecation that was ameliorated by EA at ST36 through inhibition of central and peripheral CRF signals. However, there is limited research focusing on stress-induced alterations in the small intestine, and the possible role and mechanisms of action of EA in the regulation of such dysmotility.…”
Section: Introductionmentioning
confidence: 99%